2012
DOI: 10.2223/jped.2207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of tuberculosis in children and adolescents in Rio de Janeiro

Abstract: Objective: To describe the epidemiological aspects of childhood tuberculosis (TB) in a Brazilian reference hospital. Methods:This was a retrospective study (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) of 473 subjects (0-14 year olds) with confirmed TB, or with clinical improvement by the fourth month of treatment under the unit's care, including the review of medical records, monitoring reports and notifications by the TB unit.Results: Among 473 TB cases included in the study, positive tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
2
9
0
3
Order By: Relevance
“…[7] Other studies have shown prevalence ranging from 16-56% of HIV among children with TB. [29][30][31][32][33][34][35] However, a retrospective review of TB notifications in the Kilimanjaro region of Kenya showed that of the minority of children who were tested for HIV infection, 82% tested positive. The HIV epidemic is a key factor behind the resurgence in TB incidence worldwide and HIV is the pre-eminent risk factor for the development of TB.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Other studies have shown prevalence ranging from 16-56% of HIV among children with TB. [29][30][31][32][33][34][35] However, a retrospective review of TB notifications in the Kilimanjaro region of Kenya showed that of the minority of children who were tested for HIV infection, 82% tested positive. The HIV epidemic is a key factor behind the resurgence in TB incidence worldwide and HIV is the pre-eminent risk factor for the development of TB.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, from 1999–2008, 473 children were treated at one teaching hospital, two-thirds with a known TB contact, the majority of those in the household 110. Seventeen percent were HIV-positive and a confirmed diagnosis was made in 31% of cases.…”
Section: American Regionmentioning
confidence: 99%
“…Adult contact with active disease is a vital approach in detecting TB in children. Contact rate is between 25% and 66% in various studies (21,22). Forty-one cases (45.6%) in our study had contact.…”
Section: Discussionmentioning
confidence: 44%